Conceptual Framework on Emotional Intelligence, Digital Competency, and Organizational Readiness for Change - Sopian, Bujang; Nadri Aetis Heromi, Basmawi; Diana Marie, Capel; Hasriq, Hadil (Elsevier Inc., 2022)
Competency is identified to be an essential component in determining the proficiency of an employee's skills, knowledge, and abilities. Although it is a continuously developing concept, until today scholars still debate upon the exact factors that influence employee competence. In this paper, Emotional Intelligence is recognized as a mandatory element in the assessment of employees’ competencies, which makes specific reference to an employee’s mental capability to understand their emotions. This ability enables them to attain situational awareness and make adjustments particularly for problem solving or in decision making. Salovey and Mayer's (1990) in their study discussed the concept and, developed the first model explaining the nature of Emotional Intelligence that can be used to promote intellectual growth. This conceptual paper is presented and explained in a deductive manner from general perspective to specific whilst, the purpose of systematically explaining the literature aims to produce a robust literature support. The first part of this literature launches the introduction of competency practices in the international context, followed by the presentation of literature concerning competency practices in Asia and Malaysia, whilst the third part clarifies the origins of emotional intelligence and digital competency. In addition to this, the final part of this paper encompasses the inclusion of organizational readiness for change as a mediating factor, with the conceptual framework diagram as this paper’s critical construct. This conceptual paper gives recommendation for future studies exploration into additional potential and related factors, that may influence the practice of emotional and competency profiling in the Asian context.